Teacher Supports to Facilitate the Implementation of the Good Behavior Game. (March 2020) - Coleman, Stephanie L.; Snyder, Kelly; Skinner, Lacy; Griffin, Jamie
The Good Behavior Game (GBG) is a well-established intervention for decreasing problem behaviors in the classroom. Although the GBG has a long history of both empirical support and real-world implementation, the specific types of supports teachers find useful in implementing evidence-based interventions is an area that has received increasing research attention. To help administrators, coaches, and other stakeholders devote resources with an eye toward effective implementation, this column describes training, coaching, and data collection to support the implementation of the GBG.